Thrombospondin 2/Toll-Like Receptor 4 Axis Contributes to HIF-1α-Derived Glycolysis in Colorectal Cancer - Xu, Chunjie; Gu, Lei; Kuerbanjiang, Manzila; Wen, Siyuan; Xu, Qing; Xue, Hanbing (Frontiers in Oncology, 2020)
Background:Aerobic glycolysis is a typical metabolic reprogramming in tumor cells, which contributes to the survival and proliferation of tumor cells. The underlying mechanisms controlling this metabolic switch in colorectal cancer (CRC), however, remain only partially understood. Methods: The Cancer Genome Atlas (TCGA) dataset and Gene Expression Omnibus (GEO) (GDS4382, GSE6988, GSE35834) were used to analyzed the mRNA expression of THBS2. 392 paired samples of CRC and adjacent non-cancerous tissues were collected to detect the expression of THBS2 by IHC. The correlation of THBS2 expression with categorical clinical variables in patients with CRC was evaluated using chi-square analysis or Student’s t-test. CCK-8, colony formation and animal CT scan were used to functional analysis of THBS2 in CRC. Results: Thrombospondin 2 (THBS2) is aberrantly upregulated and linked to a poor prognosis in CRC. Subsequent experiments also showed that THBS2 promotes the proliferation of CRC cells. In terms of mechanism, THBS2 interacted with Toll-like receptor 4 (TLR4), but not with the other toll-like receptors (TLRs), which upregulated the mRNA expression of GLUT1, HK2, ALDOA, PKM2, and LDHA and enhanced glycolytic capacity in CRC cells. Moreover, THBS2/TLR4 axis significantly increased the protein level of HIF-1α and blocking HIF-1α by siRNA reversed the enhanced glycolytic capacity and the upregulated expression of glycolytic enzymes in CRC cells. Conclusion: Our findings revealed that the THBS2/TLR4 axis contributes to HIF-1α derived glycolysis and eventually promotes CRC progress.